Endoplasmic reticulum composition and form: Proteins in and out. (August 2021) - Sun, Sha; Tang, Xiao; Guo, Yusong; Hu, Junjie
Abstract: The endoplasmic reticulum (ER) is the main harbor for newly synthesized proteins in eukaryotic cells. Through a continuous membrane network of sheets and tubules, the ER hosts secretory proteins, integral membrane proteins, and luminal proteins of the endomembrane system. These proteins are translated by ribosomes outside the ER and require subsequent integration into or translocation across the lipid bilayer of the ER. They are then modified post-translationally and folded in the ER. Some of these proteins are packaged into coat protein complex II–coated vesicles for export. Here, we review recent advances in understanding the mechanism of protein translocation and transmembrane domain insertion in the ER, summarize new insights into selective cargo packaging, and discuss the roles of ER morphological dynamics in these processes.